Association between CYP2C19 polymorphisms and clinical outcomes in patients undergoing stent procedure for cerebral artery stenosis - Yan-Jiao Li (Nature Portfolio, 2021)
Abstract We investigated the effect of CYP2C19 polymorphisms on the clinical outcomes of clopidogrel therapy in patients after stenting procedure for cerebral artery stenosis in northeast China. 568 patients performed CYP2C19 genotype screening in the neurosurgery department of our hospital; 154 patients were finally recruited according to the inclusion and exclusion criteria, and followed-up for 6 months. Ischemic events including (1) transient ischemic attack (TIA); (2) stent thrombosis; (3) ischemic stroke; and (4) death were defined as primary clinical endpoints. The frequencies of CYP2C19*1, *2 and *3 alleles in 568 patients were 63.1%, 31.1% and 5.8%, respectively. 154 patients were classified into extensive (65 patients; 42.2%), intermediate (66 patients; 42.9%), and poor (23 patients; 14.9%) metabolizer groups. A χ2 test showed a significant difference in primary clinical endpoints at 6 months (P = 0.04), and a multivariate Cox regression analysis indicated that the CYP2C19 loss-of-function (LOF) alleles associated with post-procedure prognosis. The Kaplan–Meier curve revealed that there was no significant difference in ischemic events between *2 and *3 alleles carriers. Our study verifies that CYP2C19 *2 and *3 have significant impact on the clinical outcomes of clopidogrel therapy in patients with stenting procedure for cerebral artery stenosis in China.